The Pandawara Group’s Participatory Communication in Environmental Activism via Social Media - Sapta Hari Subangkit; Rini Riyantini (Universitas Medan Area, 2025)
This research analyzes Pandawara Group’s participatory communication via social media for environmental activism. It focuses on their implementation of the four phases of the participatory communication program cycle: Participatory Communication Assessment (PCA), strategy design, communication activities, monitoring, and evaluation. Employing a qualitative approach with descriptive methods, data was gathered through literature reviews, Pandawara Group’s social media observation, and documentation. The results show that Pandawara Group utilizes various social media platforms to carry out participatory communication. In the PCA phase, they conduct two-way communication and gather information from the audience. Their communication strategy design involves interesting and relevant content to inspire and educate. Implementation of communication activities is carried out through various forms of content that document cleaning actions and invite involvement. Monitoring and evaluation are carried out by utilizing social media insights and interaction with the audience. In conclusion, Pandawara Group effectively employs participatory communication through social media, evidenced by high public engagement, content virality, and tangible positive impacts on environmental conservation. This research offers insights about the implementation of participatory communication in environmental activism via social media. Practically, it provides insights for the organizations engaged in the ecological on how to utilize social media to build participatory communication effectively.